2019
DOI: 10.3390/ani9121142
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Enteropathies on Commercial Farms in the Iberian Peninsula: Etiological Agents Identified in 2018–2019

Abstract: Simple Summary: Digestive disorders are the main cause of economic damage in rabbit farms and, usually, antibiotic treatment is the first choice to control them. Nevertheless, a broad range of infectious agents can be involved in such disorders, as we have observed in our diagnosis work as a veterinary diagnostic laboratory. In this study, a global and updated overview of the frequency of detection of those etiological agents is provided. We have seen differences depending on the age of the affected rabbits, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…On the opposite, the increase of SF did not modify feed efficiency, although it tended to reduce feed intake and the growth rate. The replacement of starch mainly by SF and the absence of ERE might be behind this lack of effect on feed efficiency as observed previously [26], although other authors found a positive effect [8,37,39]. These contradictory results are not explained by differences in the acid detergent fibre content [7,40], and do not seem associated to the health status.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…On the opposite, the increase of SF did not modify feed efficiency, although it tended to reduce feed intake and the growth rate. The replacement of starch mainly by SF and the absence of ERE might be behind this lack of effect on feed efficiency as observed previously [26], although other authors found a positive effect [8,37,39]. These contradictory results are not explained by differences in the acid detergent fibre content [7,40], and do not seem associated to the health status.…”
Section: Discussionmentioning
confidence: 55%
“…Digestive disorders are one of the main causes of mortality in growing rabbits, with antibiotic treatment being the usual way to control them [ 26 ]. One of the nutritional strategies to limit ERE is the inclusion of moderate levels of SF [ 3 , 6 , 27 , 28 ], while the increase of NDF might increase its incidence [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…coli and a wide spectrum of disorders, including mastitis and pododermatitis in S. aureus and P . multocida ) (Corpa et al, 2009 ; Kylie et al, 2017 ; Solans et al, 2019 ), of their role as drivers of antimicrobial usage in farmed rabbits and of the availability of some data (mostly coming from the RESAPATH and IZSVe monitoring systems, that includes > 100 isolates tested each year in the 2017–2020 period using a range of antimicrobials of interest for this opinion) indicating the presence of large (> 40%) proportions of non‐susceptible isolates to certain clinically relevant antimicrobials in the last years (Figures 4 , 5 – 9 ). Nevertheless, the limited amount of data and results found (originating mainly from only two countries, France and Italy), along with the absence of consistent reports on antimicrobial failures associated with these two pathogens and the lack of rabbit‐adapted clinical breakpoints that could help to assess the clinical significance of in vitro AST results resulted in a high uncertainty that prevented their inclusion among the most relevant antimicrobial‐resistant bacteria in rabbits in the EU.…”
Section: Assessmentmentioning
confidence: 99%
“…Clostridium spiroforme is also a relevant rabbit pathogen involved in digestive disorders, sometimes in cases of antibiotic‐associated colitis and other forms of antibiotic treatment‐related dysbiosis. This clinical presentation is very relevant in farmed rabbits (particularly in combination with other pathogens, mainly E. coli ) (Kylie et al, 2017 ; Solans et al, 2019 ) and is in fact associated with the use of antimicrobials. However, very limited information on the prevalence of resistance was available for the assessment, and the role of such resistance on the treatment of animals could therefore not be evaluated adequately therefore preventing their inclusion among the most relevant AMR pathogens in rabbits.…”
Section: Assessmentmentioning
confidence: 99%
“…In Spanish rabbitries, rabbit rotaviruses have been detected and found to often be associated with other pathogens such as Eimeria spp., C. spiroforme, C. perfringens, E. coli or combinations of these agents. The authors hypothesized that damage caused by rotavirus replication in the mucosa led to a predisposition for bacterial growth and infection [237]. Predominantly found in young farmed rabbits rotaviruses have also been described in Eastern cottontail rabbits (S. floridanus) and hares (Snowshoe and European hares).…”
Section: Rabbit Rotavirusmentioning
confidence: 99%